PRESENT PHYSICAL AND CHEMICAL FERTILITY STATE OF PALM GROVE SOILS AND THE LEVEL OF MINERAL NUTRITION OF PALM TREE (ELAEIS GUINEESIS JACQ.) FARMED IN DIFFERENT REGIONS OF CÔTE D’IVOIRE - Konan, Kouame; Severin, Ake; Wongbe, Yte; Alphonse, Kouassi N; Boake, Kone; Diabate, Sekou (European Scientific Journal, ESJ, 2014)
The diagnosis on the physical and chemical state of the palm grove soil in Côte d’Ivoire was made in different regions of the palm tree farming. For that purpose two methods were used namely the analysis of granulometric and chemical features of the soils in one hand and in other hand, the analysis of palm tree leaves in order to determine their mineral nutrition level. The question was to assess the fertility level of the soils used to farm palm tree in order to set up new fertilizer scale appropriated to the new conditions of the farming of this speculation. The analysis confirmed the lack in phosphorus and in potassium which contents vary respectively between 125 and 226 ppm and from 0.02 to 0.03 méq/100 g of soil. The contents are below the threshold of the lack in phosphorus (300 ppm) and in potassium (0.2 méq/100 g of soil). The levels of the palm tree nutrition in phosphorus and in potassium vary respectively from 0.12 to 0.18 % and 0.50 to 0.88 % of dry matter. The contents which have been obtained are below the critical threshold for these elements fixed on 1 % of dry matter for the potassium and on 0.15 % of dry matter for the phosphorus. The lack in potassium is the main chemical constraint which limits the palm tree farming in all the production area in Côte d’Ivoire. However, the nutrition level in nitrogen, calcium and magnesium are acceptable for a good growth of the palm tree. The soils of palm tree grove progresses towards a new state of chemical fertility which is more and more unfavorable to the farming unless we take necessary precautions during the preparations of the soil. Thus, it is necessary to set up a middle scale of fertilizer especially potassic appropriate to the particularities of the farming zone of palm tree in Côte d’Ivoire.